Pencarian Alel untuk Identifikasi Gen Ketahanan Penyakit Hawar Daun Bakteri, Xa7 pada Plasma Nutfah Padi Lokal Indonesia - Dwinita W Utami; Endang M Septiningsih; Triny S Kadir; Fatimah W Fatimah; Siti W Yuriyah (Jurnal AgroBiogen, 2010)
Allele Mining of Bacterial Blight Resistance Gene, Xa7 onIndonesian Local Rice Germplasm. Dwinita W. Utami,Endang M. Septiningsih, Trini S. Kadir, Fatimah, and SitiYuriyah. The abundance of novel genetic variation existingin germplasm collections is the foundation for varietyimprovement in plant breeding program. Nevertheless,studies on Indonesian genetic diversity rice germplasmusing molecular markers are still poorly. Recent advances inutilizing of simple sequence repeat (SSR) in QTL mappingand whole rice genome sequences were positive support ongenetic diversity of rice germplasm research. Based on theseadvance technology, we developed the research to discovernew alleles at important gene loci that can be used for riceimprovement. This approach is recognized as allele miningtechnology. On this study the target genes for allele miningresearch is the resistance gene for bacterial leaf blightpathogen, Xa7. This point was introduced by identify thegenetic diversity of 96 accessions Indonesian local ricegermplasm. The Xa7 allele mining was done by SNP (singlenucleotide polymorphism) designing primers based on DNAsequence around the gene target. The significant LD mapwas detected by association mapping between phenotypeand SNP genotyping data of the selected germplasm whichhaving superior performance on BLB resistance andrepresenting on genetic diversity clustering. The resultsshown that Xa7 allele variation were found in Parekaligolara(Indica, 15141), and Gajah Mada (Indica, 5856), whichresistant to BLB races IV and VIII on generative stage andfield condition. The significant Xa7-SNP8 and Xa7-SNP11markers were associating with the LD map position of Xa7gene on 28, 05-28,1Mb of chromosome 6 in rice genome.